Exploring Panic Attack Prevalence, Symptoms, Risk Factors, and Impact Among Medical Students of Islamabad; a Cross-Sectional Study - Aimen Zahra, Ujala Eman, Farah Shabbir, Atyab Faisal, Aimen Fatima, Fatima Kaleem (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
INTRODUCTION: Panic attacks are episodes of intense fear that may reflect a state of severe distress and become a risk for depression. People who experience panic attacks have impaired physical and emotional health. In medical students, these episodes interfere with their academic performance and eventually lead to burnout and decreased productivity. OBJECTIVES: To determine the prevalence of panic attacks, their relationship with associated risk factors among medical students, and to assess panic attacks’ impact on their health. METHODS: A quantitative cross-sectional study was conducted over six months among medical students enrolled at a medical college in Islamabad. The sample size was calculated to be 255 using OpenEpi. Data were collected from medical students, whereas non-medical students were excluded from the study. Data collection was mediated through a questionnaire, after obtaining approval from the ERC, containing questions related to panic attack symptoms, duration, risk factors, and impact on health. All descriptive statistics, such as chi-square tests, were applied using SPSS 31, with p<0.05 considered significant for all measures. RESULTS: The sample consisted of medical students from all five years of MBBS. Of the participants, 74.2% (n=190) had experienced the symptoms of a panic attack. Among them, 54.7% (n=140) had a panic attack for the first time after entering medical college. In addition, 44.1% (n=113) experienced panic episodes during exams or while giving a presentation. A total of 84% (n=215) considered panic attacks in some way harmful to their physical or mental health. Moreover, 45.3% (n=116) reported occasional fear and avoided places because of fear of having a panic attack. A statistically significant result was observed in the responses of the students about the impact of panic attacks on their academic and clinical performance (p<0.05). CONCLUSION: Our study reveals that panic attacks are common among medical students, with a majority experiencing onset after entering medical college. Most students perceive panic attacks as harmful to their health and note a significant impact on their academic and clinical performance, highlighting the need for targeted mental health support along with the curriculum. KEYWORDS: Panic, Prevalence, Medical Students